PROSES DOMESTIFIKASI PEREMPUAN DALAM BUDAYA ARAB (Analisis Framing Model Zhongdang Pan Dan Gerald M. Kosicki Dalam Film Wadjda) - Gita Murniasih; Diah Handayani; Taufik Alamin (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
Womendomestification has basically occurred from centuries ago. The view that women are weak creatures becomes one of the justifications of domestication behavior towards women. Wadjda film is one of the films depicting the life of Saudi women living with patriarchal cultural pressures wrapped with the teachings of Islam as a means of domesticizing women to the outside world (public). Wadjda’s film is the work of the first Saudi female filmmaker, Haifaa Al Mansour who seeks to illustrate the life of Saudi women. This study uses a gender analysis by Dr. Mansour Fakih on the manifestations of gender inequality and framing analysis of Zongdang Pan and Gerald M. Kosicki models. The results of the study indicate the occurrence of Saudi women’s domestication process which refers to the action of marginalization, stereotype, sub-ordination, double burden and polygamy. The contribution of this study is to give understanding to the women so that their awareness grow to fight for their public rights in order to get better treatment and to eliminate the negative views that have been attached to women.